2003
DOI: 10.1089/109264103322614286
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Robotics: Creating a New Program

Abstract: Objective: To share our recent experience in developing and implementing a program for computer-assisted, robot-enhanced surgery.Background: Minimally invasive surgery has revolutionized our approach to the surgical patient during the last decade. While robotic surgery does promise the ability to operate at a distance, thus providing surgical skills in remote and hazardous areas, we have found several features that could enhance our abilities as surgeons in the same room with our patient. These include tremor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…For example, Langenburg et al described a programme combining technical, financial and clinical criteria condensed in a training, implementation and development programme for surgical robotics, and found that cooperation of surgeons, staff and a corporate partner was key to the development of a successful new programme (eg, within 1 year minimally invasive surgery on a patient is performed). 30 Nisbet and Ward describe a process in which financial and technical considerations were taken into account to decide on whether to lease or purchase radiotherapy equipment. 33 Li et al ranked the factors that influence purchasing decisions and demonstrated that clinical evidence and cost-effectiveness are more important than personal preference, regardless of the stakeholder role.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Langenburg et al described a programme combining technical, financial and clinical criteria condensed in a training, implementation and development programme for surgical robotics, and found that cooperation of surgeons, staff and a corporate partner was key to the development of a successful new programme (eg, within 1 year minimally invasive surgery on a patient is performed). 30 Nisbet and Ward describe a process in which financial and technical considerations were taken into account to decide on whether to lease or purchase radiotherapy equipment. 33 Li et al ranked the factors that influence purchasing decisions and demonstrated that clinical evidence and cost-effectiveness are more important than personal preference, regardless of the stakeholder role.…”
Section: Resultsmentioning
confidence: 99%
“…In some studies, this balancing process was emphasised, but no formalised approaches were followed to achieve it. For example, Langenburg et al described a programme combining technical, financial and clinical criteria condensed in a training, implementation and development programme for surgical robotics, and found that cooperation of surgeons, staff and a corporate partner was key to the development of a successful new programme (eg, within 1 year minimally invasive surgery on a patient is performed) 30. Nisbet and Ward describe a process in which financial and technical considerations were taken into account to decide on whether to lease or purchase radiotherapy equipment 33.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not always the primary focus of the study, some made explicit that some form of approach that unifies how various purchasing stakeholders come together is important: Langenburg et al 2003, for instance, describe their new process as developing a 'vision' with paediatric surgeons, research director, a biomedical engineer and a physicist and the hospital chief executive officer, to collaborative (with industry partners) develop a short-and long-term education, research and education plan for robotic surgery. [31] Haselkorn et al (2007) also described the importance of an organizational culture as a crucial component for success in the procurement process. [29] Regardless of it being a cultural or difference in vision, fundamental differences in purchasing projects can be identified.…”
Section: Resultsmentioning
confidence: 99%
“…[27] A suggestion to streamline the management process is the implementation of a management information system described by Larios et al 2000,[32] where necessary information for specification and selection of medical equipment can be documented and it is found to improve timeliness, procedural efficiency, consistency and information integration. For the development of new programs a business plan is essential), according to two studies [29,31] and proper planning and management can result in prevention of unnecessary buying according to Verma and Peacock 2014. [47] With regards to tendering, Satta et al 2019 described a process in which stringent specifications were laid out in a tender specifications for an ophthalmic surgery femtosecond laser, but note the disadvantage that their whole process of laying such specific specifications and conducting trials took about 4 years.…”
Section: Resultsmentioning
confidence: 99%